The changing world under the corona virus threat—from human needs to SDGs and what next?. Issue 1 (2nd January 2021) - Altan, Orhan; Dowman, Ian
ABSTRACT: The COVID-19 (coronavirus) disease has affected over 100 countries in a matter of weeks. The way humans live and work on planet Earth has changed profoundly over the last months. Many lives and livelihoods have been lost. Ways of working, shopping, and social interactions are all vastly different for most of us. We do not know when the current crisis will end, or how far we will "return" to the way things were before the pandemic. The world is experiencing one of the most transformative moments of the last 100 years. The social, economic, and political influences of the COVID-19 crisis have already been hugely momentous, we do not utterly understand it. Looking ahead, we have inevitably had to make important public health, economic, governance, and ecological decisions with less information than usual and to reverse recently adopted policies, which can lead to an era of disruptive transformations to sustainability. During these historic times, we must understand the hidden reality of the earth system and attempt to transform our needs so that we all have a sustained future on our planet.